Does the OTA Open Fracture Classification Predict the Need for Limb Amputation? A Retrospective Observational Cohort Study on 512 Patients. Issue 4 (April 2016) - Hao, Jiandong; Cuellar, Derly O.; Herbert, Benoit; Kim, Ji Wan; Chadayammuri, Vivek; Casemyr, Natalie; Hammerberg, Mark E.; Stahel, Philip F.; Hak, David J.; Mauffrey, Cyril
Abstract : Background: Few studies have examined the utility of the Orthopaedic Trauma Association Open Fracture Classification (OTA-OFC) compared to the traditional Gustilo-Anderson classification for prediction of treatment outcomes in patients with open fractures. Questions/Objectives: (1) How do the Gustilo-Anderson classification and OTA-OFC systems compare in accuracy of predicting limb amputation, infection, and need for soft tissue coverage? (2) Is there an OTA-OFC summative threshold score that may guide the discussion and decision-making with regard to limb salvage or amputation? Design: Retrospective observational cohort study; Level IV evidence. Setting: Level I trauma center and urban safety-net institution. Patients/Participants: Consecutive adult patients with open long bone fractures who underwent operative treatment between January 1, 2007 and December 31, 2012. Main Outcome and Measurements: Postoperative complications of infection, early limb amputation, and requirement for soft-tissue procedures. Results: The study cohort comprised 512 patients with mean age 49.6 ± 14.9 years. Nineteen patients (3.7%) underwent amputation. The Gustilo-Anderson classification demonstrated no correlations with any of the primary outcome measures, while OTA-OFC summative scores significantly varied between all outcome comparison groups. The skin injury component of the OTA-OFC was an independent predictor of limb amputation (OR, 5.44; 95% CI, 2.37–12.47), and an OTA-OFC summative score of ≥10 best correlated with need for amputation ( P < 0.001). Sensitivity and specificity of the reported model were 79% and 94%, respectively. Conclusions: Our results should be interpreted with caution due to the retrospective nature of our study. Based on our data, the OTA-OFC is superior to the Gustilo-Anderson classification system for prediction of postoperative complications and treatment outcomes in patients with open long bone fractures. A summative threshold score of 10 seems to identify increased odds of successful limb salvage.